2021
DOI: 10.3389/fonc.2021.632176
|View full text |Cite
|
Sign up to set email alerts
|

A CT-Based Radiomics Nomogram for Preoperative Prediction of Lymph Node Metastasis in Periampullary Carcinomas

Abstract: PurposeTo establish and validate a radiomics nomogram for preoperatively predicting lymph node (LN) metastasis in periampullary carcinomas.Materials and MethodsA total of 122 patients with periampullary carcinoma were assigned into a training set (n = 85) and a validation set (n = 37). The preoperative CT radiomics of all patients were retrospectively assessed and the radiomic features were extracted from portal venous-phase images. The one-way analysis of variance test and the least absolute shrinkage and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…However, the judgement of LN metastasis in CT was mainly based on the enhanced and margin status and other indicators, which had certain subjective dependence. Previous studies have discovered the low accuracy of CT for assessing peripancreatic LNM (63%-81%), which was similarly confirmed in our study (66.7%) [ 24 , 25 ]. Although some radiological features such as parenchyma atrophy and extrapancreatic perineural invasion status have been documented as significant prognostic indicators of PDAC, there were no statistical differences between high and low Ki-67 expression sets and still inability to be used as predictors of Ki-67 expression.…”
Section: Discussionsupporting
confidence: 91%
“…However, the judgement of LN metastasis in CT was mainly based on the enhanced and margin status and other indicators, which had certain subjective dependence. Previous studies have discovered the low accuracy of CT for assessing peripancreatic LNM (63%-81%), which was similarly confirmed in our study (66.7%) [ 24 , 25 ]. Although some radiological features such as parenchyma atrophy and extrapancreatic perineural invasion status have been documented as significant prognostic indicators of PDAC, there were no statistical differences between high and low Ki-67 expression sets and still inability to be used as predictors of Ki-67 expression.…”
Section: Discussionsupporting
confidence: 91%
“…In one previous studies, Bi et al established and validated a radiomics nomogram for preoperatively predicting LNM in PCs. The results showed that the radiomics nomogram incorporating radiomics signature and CT-reported LN status obtained favorable discrimination and calibration ability in both training and validation set, with AUC of 0.853 for each set [22]. However, although the radiomics nomogram performed well, it was complicated and timeconsuming, to some extent.…”
Section: Discussionmentioning
confidence: 98%
“…Two radiologists (observer 1 and observer 2, with 8 and 15 years of experience in abdominal MR interpretation, respectively) reviewed all images in consensus. The following image features were evaluated: 1) tumor size, de ned as the lesion's maximum diameter on axial images; 2) vascular involvement, de ned as vessel occlusion, stenosis, or contour deformity due to tumor invasion; and 3) LNM, de ned as LN's short-axis diameter larger than 10 mm, or LNs with central necrosis, or LNs were hyperenhanced than liver parenchyma in portal venous phase [21,22]. The observers knew that all patients were diagnoses of PC but were blind for the clinical and pathological details.…”
Section: Mr Feature Evaluationmentioning
confidence: 99%
“…Hence, to improve the diagnosis of DPC and its TNM stage, comprehensive diagnosis should include a combination of other clinical characteristics and new technologies. To our knowledge, few studies have constructed models to predict LNM and survival in patients with duodenal malignant tumours via radiomics analysis [23]. Previous studies have shown that T stage and lymph vessel invasion are independent risk factors for LNM [24][25][26].…”
Section: Discussionmentioning
confidence: 99%